Coupling spatialised models to evaluate the effects of urban densification on air quality in the Paris metropolitan area. (2017) - Prud'homme, Julie; Coll, Isabelle; Etuman, Arthur Elessa; Viguié, Vincent; Coulombel, Nicolas
Compact city concept has been widely debated and analysed in scientific literature. Many methodologies have been established, in which the air quality issue was more or less studied. In this article, we propose a methodological perspective that identifies the impact of territorial policies, socio-economic parameters, energy consumption constraints and urban shape on the structure of anthropogenic emissions, and thus on urban and suburban air quality on the case of the Paris metropolitan area (France). To do so, we use a spatialised modelling chain designed to explore the interactions between urban shape and pollutant concentrations in the atmosphere.